Congenital biliary atresia in a Beefmaster calf - Ruíz-Ramírez, Johnatan A.; García-Márquez, Luis J.; Bedolla-Alva, Mario A.; Salas-Garrido, Gerardo; Ramírez-Romero, Rafael; Julio; López-Mayagoitia, Alfonso (Brazilian Journal of Veterinary Pathology, 2016)
Biliary atresia is a congenital cholangiopathy characterized by a progressive fibrosis of the bile ducts leading to impaired biliary flow, hepatic failure, icterus and early death. This paper describes the gross and microscopic findings in a 4-week-old Beefmaster calf that unexpectedly died with severe jaundice. On postmortem examination, the liver was firm in texture and exhibited an orange-yellow discoloration. Microscopically, there were cholestasis, hyperplasia, fibrosis and obliteration of the bile ducts, and mural fibrosis of the gall-bladder. Masson’s trichrome and Gomori’s stain revealed excessive collagen deposition in the portal areas and biliary ducts, and occasionally around central veins. Immunohistochemistry confirmed biliary epithelial cells, not only lining the bile ducts but also were forming tubular-like structures devoid of a lumen. Blood test was negative for babesiosis and anaplasmosis. Based on these findings, the final diagnosis was congenital biliary atresia.